Who is "energy poor" in the EU? - Sofia Maier; Ilda Dreoni (European Commission, Joint Research Centre (JRC), 2024)
With the hike of global energy prices of 2022-2023 and the fairness challenges of the green transition, energy poverty is again back to the forefront of economic policy debates in Europe. However, the absence of consensus on energy poverty measurement complicates policy formulation and evaluation in this domain. This paper conducts a comprehensive analysis of the EU-wide distribution and profiles of the 'energy poor'. We use four well-known measures of energy poverty, two subjective and two based on expenditures, coming from two different household surveys, i.e., HBS and SILC, which we statistically match. With this, we fill an important gap in the literature by measuring the extent of overlap between these indicators. Our results reveal that expenditure-based indicators cover larger shares of the population, especially in middle and high-income EU countries, with very small overlap between energy poverty measures. In the EU, only 0.3% of the population qualifies as 'energy poor' when considering all four indicators, while four out of ten (40%) would enter this club by at least one of these indicators. Overall, by providing a characterization of the profiles of those who would be covered or 'left behind' by each of these indicators, as well as their relationship with incomes and expenditures, we shed new light on the heterogeneous distributional effects from policy-targeting based on these indicators.
Keywords: C81; D31; H20; H22; 330; energy poverty; European Union; SILC; HBS